Acrania: Two case reports with prenatal ultrasound results - Koç, Mustafa; Akbaş, Gökhan (My University, 2008)
Acrania is a rare congenital anomaly and characterized by partial or complete absence of the calvarium with abnormal brain tissue development. The pathogenesis of acrania is unknown and differential diagnosis should be searched to rule out other similer conditions to anencephaly and acalvaria. Diagnosis of cranial bone defects can be established by ultrasonography in the first trimester of pregnancy. We report two cases, diagnosed prenatally by ultrasonography, one with isolated acrania and the other one associated with meningocele.
Keywords: Acrania; Prenatal diagnosis; Ultrasonography, prenatal